Determinants of risk factors for the development of obstetric fistula in a national fistula centre of a tertiary care medical college hospital - Nath, Sukla; Dutta, Surajit; Ferdous, Riasona; Karim, Ataul; Siddiqua, Quazi Aysha; Shameem, Musarat; Siddiqee, Rojy; Ara, Iffat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Obstetric fistula is a debilitating condition caused by prolonged, obstructed labor without timely medical care, creating an abnormal opening between the birth canal and bladder or rectum. It remains prevalent in developing regions, particularly South Asia and Africa, due to early marriage, poor maternal healthcare, and lack of skilled birth attendants. In Bangladesh, obstetric fistula is both a medical and social burden, demanding targeted public health interventions. Objectives were to identify the risk factors and patient profile associated with obstetric fistula among women attending the national fistula centre, Dhaka medical college hospital (DMCH), Dhaka, Bangladesh. Methods: This case-control study was conducted in the department of obstetrics and gynaecology at DMCH from July to December 2010. A total of 50 confirmed obstetric fistula cases were selected using purposive sampling. Data were collected via structured questionnaires and clinical examination. Inclusion and exclusion criteria were strictly followed. Data analysis was done using SPSS software. Ethical approval and informed consent obtained before initiating study. Results: Among respondents, 34% were aged 31-35 years. In control group, 82% were aged 21-30. Inhabitants: 66% urban in control, 76% rural in case group. Education: 64% control crossed SSC; 42% case were illiterate. Labour pain >24 h in 94% cases. Home trial >24 h in 92% cases. Delivery by Dai: 87.5% in cases. Caesarean section: 58% in cases vs 6% in control. Assisted deliveries: 84.62% in cases. Conclusions: Early marriage, poor health behavior, malnutrition, and lack of ANC contribute to obstetric fistula, with delayed hospital visits.